Research on atmospheric air quality in the Prykarpattia region - Moisuk, Mykola; Hurei, Mykhailo; Ovsianetska, Diana (Видавництво Львівської політехніки, 2025)
The goal of this study was to assess and analyze the air quality on the territory of the Ivano-Frankivsk National Technical University of Oil and Gas, evaluate pollution levels, and identify the main sources of harmful emissions. The study was conducted on the territory of the university, where measurements of the main atmospheric air parameters were carried out using the multifunctional device FLUS 5-in-1, the gas detector Walcom W-K-600, and the CEM GD-3803 instrument. Parameters such as wind speed, air temperature and humidity, light intensity, and concentrations of formaldehyde, nitrogen oxide, carbon dioxide, carbon monoxide, and oxygen were measured. A systematic approach was applied with an even distribution of measurement points across the university territory, including areas with high traffic, academic buildings, and green zones. As a result of the study, no excess gases concentrations were recorded. The practical value of the study lies in the development of recommendations to improve air quality, including optimizing traffic flows, increasing green zones, and implementing modern air purification technologies. Further research should focus on a detailed analysis of the impact of different pollution sources and the development of innovative technologies to reduce harmful emissions. The results of this study confirm the relevance of the issue and the need for systematic monitoring of atmospheric air quality, as well as the implementation of effective measures to reduce pollution, which is crucial for improving living conditions and public health.
Keywords: air pollution; harmful emissions; environmental situation; anthropogenic pollution; environmental quality monitoring